Uma análise do ensino de proporcionalidade no ensino fundamental : realidade e perspectivas - Silva, Davidson Moura Lopes (Universidade Federal de São Carlos, 2015)
This work presents a new proposal of approach for proporcionality, whose focus is the Brazilian Elementary 7th grade student. This work is the record of a work of didactic engineeering that generated a sequence made by four didactic sessions. The main goal of this dissertation is to present ways for the student to determine, based on mathematical de_nitions, if two magnitudes are proportional and, in a_rmative case, if the relation is directly or inversely proportional. In order to do so, we propose the employment of a software called Geogebra as a teaching tool, to allow the integration with geometry, direct and inverse proportionality relations and practical experiments to assign a greater meaning to the presented content.
Keywords: Ensino fundamental; Proporcionalidade; Engenharia didática; Geogebra; Proportionality; Elementary education; Didactic engineering; CIENCIAS EXATAS E DA TERRA::MATEMATICA